Proline accumulation in pigweed plants (Amaranthus dubius Mart, and Amaranthus cruentus L.) growing under water stress conditions - Ferrarotto, M. (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2011)
Many plants accumulate high levels of proline (Pro) in response to water stress, and this is noticeably evident in some mesophytic flowering plants. Generally, these levels are higher than those required to be used in protein synthesis. Even though Pro can act as an osmoprotectant, the increases in pool sizes of metabolites in stressed tissues do not necessarily connote adaptive significance. Amaranthus dubius is widely distributed as a weed in tropical regions, showing a high competitive capacity due to its high growth rate and efficient water extraction from the soil. However, in situ observations show that A. dubius wilts rapidly during laboratory manipulation or when submitted to short water stress periods. The selection of Amaranthus cruentus for this study was made on the basis that this species has been reported as drought tolerant. In this study, plants of A. dubius and A. cruentus were grown under water stress conditions (S) in order to determine if differences in the response in both species were related to Pro accumulation. Water hidric potential ( í¸) and relative water content (RWC) were determined. The Pro concentration on a fresh weight basis was determined colorimetrically. Dehydration was higher in A. dubius plants in S, and free Pro increased in both species.